Surface dual-shell construction enhances the electrochemical performances of Li1·2Ni0·13Co0·13Mn0·54O2 cathode materials. (1st May 2020) - Chen, Yongxiang; Li, Yunjiao; Zheng, Junchao; Li, Wei; Luo, Linshan; Yang, Jiachao; Liu, Shuaiwei; Xiong, Yike; Wang, Shan
Abstract: High-capacity lithium- and manganese-rich cathodes play a critical role in the development of the advanced Li-ion batteries. However, the severe capacity fading and voltage decay impede their commercial applications. Herein, the vacancy-enriched Li1·2 Ni0·13 Co0·13 Mn0·54 O2 cathodes with spinel/defective structure shell are realized by the gas-solid reactions (GSR) and the followed Li–Nb–O coating shell coated Li1·2 Ni0·13 Co0·13 Mn0·54 O2 cathodes are achieved by a liquid coating process (LCP). The dual-shell modified Li1·2 Ni0·13 Co0·13 Mn0·54 O2 cathodes can deliver 219.5 mAh·g −1 at 250 mA g −1 and corresponding to 96.44% capacity retentions after 100 cycles over 2.0–4.6 V, far higher than those (212.3 mAh·g −1 and 83.09%) of the pristine Li1·2 Ni0·13 Co0·13 Mn0·54 O2 cathode material. Even at 1250 mA g −1, the capacity retentions also improve from 50.68% to 95.92% after 100 cycles. The enhanced electrochemical performances are mainly ascribed to the enhanced structural stability and the suppressed harmful side-reactions/transition metal dissolutions. The construction of the dual shells provides an effective method to optimize the interfacial structure of Li- and Mn-rich cathode material and other cathode materials. Highlights: The spinel/defective shell coated Li-rich cathodes are constructed by GSR process. Li–Nb–O shell coated Li-rich cathodes are prepared by the liquid coating process. The. The dual shells enhance the bulk/interfacial structures and lithium kinetics. The study provides an effective method to optimize the structure of Li-rich cathode.